Problem-Based Learning: Cervical Adenocarcinoma Three-Session Case for First-Year Medical Students-Patient Minnie Pauls - Blair Suter; Heimo Riedel (Association of American Medical Colleges, 2017)
Introduction Cervical adenocarcinoma represents a critical health problem in many underserved regions of the world and parts of the U.S. This module provides learning opportunities in the areas of female anatomy, physiology, histology, and pathology. This includes diagnosis by ultrasound and CT/PET scan, detailed staging and treatment of the cancer by various criteria, and future prevention by vaccination and screening. Methods Authors include a fourth-year medical student and a seasoned PBL facilitator with a basic science interest in cancer. In this problem-based learning module (PBL), a group of first-year medical students review the material that is released online for each of three weekly 90-minute sessions. Key learning issues are identified, researched out-of-class, and discussed at the beginning of the subsequent session. A differential diagnosis is weighed and the module culminates with a concept map drawn by students to integrate all relevant aspects and mechanisms of the case. Results The module was implemented twice with a small group of seven students. Students learned to correlate relevant biochemical mechanisms, histological, and anatomical features with the clinical signs and symptoms, to diagnose and suggest treatment options. The module was well-liked, and revised for publication by rebalancing the material based on specific student feedback. Discussion The PBL small-group format provides a unique opportunity over both semesters for first-year medical students to study clinical cases in a student-directed fashion and develop professional skills at various levels. Potential pitfalls lie in the online format, as this requires clear rules on computer usage and data sharing.